Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) pada Topik Siklus Makhluk Hidup untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik Kelas III Sekolah Dasar - Nanin Ilahi; Endang Widi Winarni; Osa Juarsa (UNIB Press, 2026)
The type of research employed was Research and Development (R&D), utilizing the ADDIE development model, which includes the analysis, design, development, implementation, and evaluation stages. The data collected comprised both quantitative and qualitative data. Quantitative data were obtained from the validation results by material, language, and graphic experts, product trials, and effectiveness testing via pretest and posttest. Qualitative data were gathered from interviews, observation, and response questionnaires administered to teachers and students. The research results indicated that the developed PBL-based Student Worksheet was deemed feasible for use according to the material, language, and graphic expert validators. The responses from both teachers and students were classified as very positive regarding the media's appearance and ease of use. Furthermore, the effectiveness test results showed an increase in students' problem-solving abilities, with an N-Gain Score of 0.6648, which falls into the high category. Based on these findings, it can be concluded that the PBL-based Student Worksheet is effective for improving the cognitive learning outcomes of third-grade elementary school students.